Paramagnetic particles coupled with an automated flow injection analysis as a tool for influenza viral protein detection - Krejcova, Ludmila; Dospivova, Dana; Ryvolova, Marketa; Kopel, Pavel; Hynek, David; Krizkova, Sona; Hubalek, Jaromir; Adam, Vojtech; Kizek, Rene (Electrophoresis, 2012)
Currently, the influenza virus infects millions of individuals every year. Since the influenza virus represents one of the greatest threats, it is necessary to develop a diagnostic technique that can quickly, inexpensively, and accurately detect the virus to effectively treat and control seasonal and pandemic strains. This study presents an alternative to current detection methods. The flow-injection analysis-based biosensor, which can rapidly and economically analyze a wide panel of influenza virus strains by using paramagnetic particles modified with glycan, can selectively bind to specific viral A/H5N1/Vietnam/1203/2004 protein-labeled quantum dots. Optimized detection of cadmium sulfide quantum dots (CdS QDs)-protein complexes connected to paramagnetic microbeads was performed using differential pulse voltammetry on the surface of a hanging mercury drop electrode (HMDE) and/or glassy carbon electrode (GCE). Detection limit (3 S/N) estimations based on cadmium(II) ions quantification were 0.1 μg/mL or 10 μg/mL viral protein at HMDE or GCE, respectively. Viral protein detection was directly determined using differential pulse voltammetry Brdicka reaction. The limit detection (3 S/N) of viral protein was estimated as 0.1 μg/mL. Streptavidin-modified paramagnetic particles were mixed with biotinylated selective glycan to modify their surfaces. Under optimized conditions (250 μg/mL of glycan, 30-min long interaction with viral protein, 25°C and 400 rpm), the viral protein labeled with quantum dots was selectively isolated and its cadmium(II) content was determined. Cadmium was present in detectable amounts of 10 ng per mg of protein. Using this method, submicrogram concentrations of viral proteins can be identified.
Keywords: Flow Injection Analysis; kvantové tečky; elektrochemické techniky; Streptavidin; magnetické nanočástice; kadmium; Hemagglutinin Glycoproteins, Influenza Virus; Biotin; Magnetite Nanoparticles; Sulfides; elektrody; Mercury; uhlík; hemaglutininové glykoproteiny viru chřipky; Biosensing Techniques; virus chřipky A, podtyp H5N1; Cadmium; průtoková injekční analýza; sulfidy; Linear Models; Electrochemical Techniques; rtuť; sloučeniny kadmia; Electrodes; biosenzitivní techniky; Influenza A Virus, H5N1 Subtype; Quantum Dots; streptavidin; Limit of Detection; Carbon; lineární modely; limita detekce; Cadmium Compounds; biotin